2002
DOI: 10.1053/jhep.2002.34136
|View full text |Cite
|
Sign up to set email alerts
|

Embryoid-body cells derived from a mouse embryonic stem cell line show differentiation into functional hepatocytes

Abstract: Embryonic stem (ES) cells have a potential to differentiate into various progenitor cells.Here we investigated the differentiation capacity of mouse ES cells into hepatocytes both in vitro and in vivo. During the culture of embryoid bodies (EBs) derived from ES cells, albumin (ALB) messenger RNA (mRNA) was expressed within 12 days after removal of leukemia inhibitory factor, and ␣-fetoprotein (AFP) mRNA was observed within 9 days without additional exogenous growth factors. In ES cells and early EBs, by contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
212
4
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(219 citation statements)
references
References 30 publications
1
212
4
2
Order By: Relevance
“…The information that has been generated by the study of hepatic development is also now being used in the production of hepatocytes and other liver cells from progenitor cell populations and embryonic stem cells. 124,[153][154][155] For example, Teratani and colleagues demonstrated that embryonic stem cells could be induced to generate cells with hepatic gene expression profiles and functions using a differentiation procedure that included culture with FGF, hepatocyte growth factor, and oncostatin M. 156 The ability to efficiently produce hepatocytes from progenitor or embryonic stem cells is exciting, because such cells could potentially be used for hepatocyte transplantation, gene therapy, the generation of artificial liver devices, or even tissue engineering. [157][158][159] By building on our understanding of the basic mechanisms that lead Fig.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…The information that has been generated by the study of hepatic development is also now being used in the production of hepatocytes and other liver cells from progenitor cell populations and embryonic stem cells. 124,[153][154][155] For example, Teratani and colleagues demonstrated that embryonic stem cells could be induced to generate cells with hepatic gene expression profiles and functions using a differentiation procedure that included culture with FGF, hepatocyte growth factor, and oncostatin M. 156 The ability to efficiently produce hepatocytes from progenitor or embryonic stem cells is exciting, because such cells could potentially be used for hepatocyte transplantation, gene therapy, the generation of artificial liver devices, or even tissue engineering. [157][158][159] By building on our understanding of the basic mechanisms that lead Fig.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…that ES cells can be differentiated into hepatocyte-like cells [1][2][3][4][5][6] . ES cell-derived hepatocytes would be useful as a source of material for cell transplantation, bioartificial liver (BAL) support devices, studies on hepatocyte biology and hepatitis viruses and for drug testing.…”
Section: Protocols Have Been Developed To Differentiate and Enrich Vamentioning
confidence: 99%
“…Several studies have reported the induction of ES cell differentiation into hepatocytes both in vitro [6][7][8][9] and in vivo. 10 The in vitro approaches involve the formation of embryoid bodies (EBs) to re-create the inductive microenvironment required for liver organogenesis 11,12 or treatment with specific growth factors and cytokines critical for hepatocyte differentiation such as hepatocyte growth factor, fibroblast growth factor, and oncostatin. 1,13 Also, the introduction of genes promoting endodermal differentiation into ES cells, 14 modification of culture microenvironment by supplementation with extracellular matrix proteins or coculture with other cell types, 15,16 is used to direct ES cells toward a hepatocytic lineage.…”
Section: -1486)mentioning
confidence: 99%